Life expectancy by education, income and occupation in Germany: Estimations using the longitudinal survival method. - (:unkn) unknown (Bundesinstitut für Bevölkerungsforschung, 2015)
Reliable estimates for differences in life expectancy (LE) by socio-economic position (SEP), that can be assessed in an international context and are comprehensive in terms of considering different SEP dimensions, are missing for the German population so far. The aim of the present study is to fill this gap by providing estimates for differences in LE by education, household income, work status and vocational class. The lack of national mortality data by SEP required an innovative methodological approach to estimate LE from survey data with a mortality follow-up. The main strengths of the method are the low demand on the data, its simple applicability and the estimation of a set of age-specific probabilities of dying. We employed the method to the German Life Expectancy Survey and estimated period life tables for 45 male and 32 female SEP subpopulations. The results show striking differences in LE across all analysed SEP indicators. Among men, LE at age 40 ranges by more than five years between the lowest and highest household income quartiles, more than six years between individuals with low and high education, around ten years across the work status groups, and almost 15 years across the vocational classes. The proportion of those who reach the classic pension age of 65 years also varies considerably, as does the remaining LE at this age. The corresponding differences among women are smaller, yet still notable. The results yield an interesting finding for the ongoing discussion about the various consequences of an increased pension age. Moreover, they provide policy-makers, doctors, researchers and public health workers with insights into Germany's most disadvantaged SEP subpopulations and the potential extent of their disadvantages in terms of longevity and mortality.
Keywords: Bevölkerungsentwicklung; Bevölkerungsprognose; Beruf; Bildung; Einkommen; Demographischer Wandel; Lebenserwartung; Längsschnittuntersuchung; Mortalität; Einflussfaktor; Haushaltseinkommen; Soziale Ungleichheit; Benachteiligung